1971
DOI: 10.1111/j.1745-3984.1971.tb00901.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Unwarranted Confidence in Responses to Objective Test Items

Abstract: Investigated were the effects of several variables on the expression of unwarranted confidence in the accuracy of responses to objective test items. A final examination was administered to 72 subjects under confidence-weighting instructions with two levels of penalty for incorrect responses. A 2-way ANOVA revealed no significant main effects or interaction attributable to level of penalty or sex. Although increased penalty level had no effect on confidence-expression, the test's reliability decreased from .85 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Overall, the choice weighting approaches have produced little in the way of increased re liability or validity of measurement (e.g., Diamond, 1975;Kasup and Hakstian, 1975;Hasen, 1971;Jacobs, 1971). Rippey (1970) compared five such approaches and summarized the re sults as follows: "Comparison between reliabilities showed that the simplest and most intui tive function, the probability assigned to the correct answer, produced the highest reliabil ity.. . "…”
Section: Discussionmentioning
confidence: 98%
“…Overall, the choice weighting approaches have produced little in the way of increased re liability or validity of measurement (e.g., Diamond, 1975;Kasup and Hakstian, 1975;Hasen, 1971;Jacobs, 1971). Rippey (1970) compared five such approaches and summarized the re sults as follows: "Comparison between reliabilities showed that the simplest and most intui tive function, the probability assigned to the correct answer, produced the highest reliabil ity.. . "…”
Section: Discussionmentioning
confidence: 98%
“…It is possible to devise optimum strategies for answering with confidence systems that do not have the reproducing property of Shuford, Albert, and Massengill. A final evaluation of confidence testing must weigh the gain in ability variation against the gain in error variation. The studies of Jacobs (1971), Hansen (1971), and Swineford (1938Swineford ( ,1941 lead one to conclude that there is a personality factor of "general confidence" operating in the confidence testing procedure which contaminates the results yielding an increase in error variation. Shuford and Massengill (1969) have claimed that this factor can be eliminated or at least considerably reduced with practice using their SCoRule device although there exists little data to support such a claim.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Ziller (1957) suggested an alternative method for determining a similar score from similar data. Jacobs (1971) has questioned the use of confidence weighting on the grounds that the scoring procedure tends to be contaminated by individual differences in personality. For other studies using confidence testing in personality research see Kogan and Wallach (1964) and Slakter (1967Slakter ( ,1968.…”
Section: Confidence Weighting Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…These marking schemes had the disadvantages of being "complicated to score, requiring pretraining in the format for the students, and confounding of scores with personality dimensions, in so far as some types of personality are more prone to expressing unwarranted confidence (Hansen, 1971;Jacobs, 1971). This sort of test scoring has not been used for large scale testing purposes, possibly because of these disadvantages.…”
mentioning
confidence: 95%